2019
DOI: 10.1080/08941920.2019.1648710
|View full text |Cite
|
Sign up to set email alerts
|

Synthesizing Conservation Motivations and Barriers: What Have We Learned from Qualitative Studies of Farmers’ Behaviors in the United States?

Abstract: Since 2011, qualitative studies examining adoption of conservation practices and programs (CPPs) have burgeoned. This article presents a systematic review of all U.S.-based qualitative investigations into CPP adoption since 1996. We found three themes are discussed primarily as motivating adoption: farmer characteristics, environmental awareness, and trust in information sources. Four themes are discussed primarily as barriers to adoption: farm management, negative perceptions of a conservation practice, perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 150 publications
(117 citation statements)
references
References 68 publications
(58 reference statements)
4
97
0
1
Order By: Relevance
“…The conventional tillage had higher costs of fuel and labor. This indicates that cost savings on no‐till may promote growers to use more conservation tillage, while an increase in production cost may be a barrier for cover crop adoption (Prokopy et al., ; Ranjan et al., ).…”
Section: Restults and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional tillage had higher costs of fuel and labor. This indicates that cost savings on no‐till may promote growers to use more conservation tillage, while an increase in production cost may be a barrier for cover crop adoption (Prokopy et al., ; Ranjan et al., ).…”
Section: Restults and Discussionmentioning
confidence: 99%
“…The advantages of adopting NT and cover crops include retaining crop residues on the soil surface, increasing soil organic matter and nutrients, improving water holding capacity, reducing water evaporation, and mitigating soil erosion (Cates & Jackson, 2018;Dabney, Delgado, & Reeves, 2001;Daryanto, Fu, Wang, Jacinthe, & Zhao, 2018;Snapp et al, 2005;Triplett & Dick, 2008). Studies have reviewed the adoption of NT in the United States Ranjan, Church, Floress, & Prokopy, 2019) and concluded that NT resulted in improvements in soil properties, greater cropping intensity, and higher crop productivity (Hansen, Allen, Baumhardt, & Lyon, 2012;Wallace et al, 2017). Agronomic and economic influences of cover crop adoption have been evaluated in studies of different cropping systems (Lewis et al, 2018;Schomberg et al, 2014;Zhou, Larson, Boyer, Roberts, & Tyler, 2017).…”
mentioning
confidence: 99%
“…As farm size increases and landowners age, single landowners (or families) often cannot manage the entire farm, which is a contributing factor to a nationwide report that found 54% of cropland was operated by renters in 2014 (Bigelow, Borchers, & Hubbs, ). These renters do not have a family tie or connection to the land that the owners do and, in many cases, are less interested in long‐term benefits of multifunctional land management and more influenced by market prices in cropping decisions (Ranjan, Church, Floress, & Prokopy, ; Wang et al., ; Wimberly et al., ). Additionally, the larger farms, whether managed by renters or owners, are typically more influenced by federal policy and are more likely to convert land based on legislation (Wimberly et al., ).…”
Section: Why Are Cropping Patterns Changing?mentioning
confidence: 99%
“…Another barrier is that conversion to reduced tillage or cover crop systems may require purchase of new equipment and training on different farming techniques (Awada et al., ). However, because many producers in the region already practice reduced tillage, adopting this practice may be more straightforward because it will be culturally acceptable, and newcomers may have the benefit of learning from nearby current practitioners (Ranjan et al., ).…”
Section: What Strategies May Be Useful To Create More Balanced Agroecmentioning
confidence: 99%
See 1 more Smart Citation